AN ANALYSIS OF THE DETERMINANT FACTORS INFLUENCING FOLLOWER ENGAGEMENT ON THE INSTAGRAM ACCOUNT RS ROYAL SURABAYA - Leatemia, Putri Daniella Natalia; Kurniawan, Daniel (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the factors that influence engagement among followers of the Instagram account @rsroyalsurabaya. Engagement is a key indicator in digital marketing strategies, as it reflects the level of audience interaction and involvement with posted content. The factors examined in this research include content quality, posting consistency, admin responsiveness,and the relevance of information to audience needs. A quantitative descriptive method with an explanatory research approach was used. Data were collected through questionnaires distributed to 200 active followers of @rsroyalsurabaya, selected using purposive sampling. Multiple linear regression analysis was applied to determine the influence of each factor on engagement. The findings show that content quality, posting consistency, and admin responsiveness significantly affect follower engagement. Among all variables, the relevance of information was identified as the most dominant factor in shaping engagement.